The Powerful, the Poor, and the Politics of Representation in Luis Estrada's Un mundo maravilloso (2006). - Robinson, Amy (Studies in Latin American Popular Culture, 2014)
This article examines the transformation of the film Un mundo maravilloso's poor protagonist from a bumbling picaro to a rebel capable of inverting center and periphery. I explain the director's use of metafictionality, selfreferentiality, and intertextuality that compels spectators to become active participants in the film's critique of the dominant metanarratives about the poor in Mexico. My aim is to reveal the way the film prods spectators to reflect on how understandings of the poor are mediated through representations that distort and dismiss reality. Spectators are compelled to see through the elites' misleading rhetoric and false images, and they instead discern the mechanisms in place that obscure the realities of poverty, mask the failures of political leadership, and encourage the complicity of everyday Mexicans in the dismissal of the poor from the national landscape. Through the poor characters' transgressions, the audience is left to consider how, despite the seemingly overwhelming power of the elite to fabricate the dominant scripts about the poor, the power to tell one's own story can be reclaimed through the spectacles of an active rebel seeking redress or of an untetbered madman with utter disregard for societal constraints.